Prevention of osteoporosis by reestablishing the balance via extracellular vesicles - Dr Xiaoyuan Huang; Dr. Yanhua Lan; Prof. Zhuo Chen; Prof.Zhijian Xie (Elsevier, 2023)
Aim or Purpose: Chronic inflammatory status is an essential aspect of aging, pro-inflammatory cytokines lead to massive upregulation of osteoclast function and subsequent osteoporosis. Osteoclast precursors (OCPs) are thought to commit to osteoclast differentiation, but whether they have sufficient functional plasticity to transit into other cell lineages is unknown. Herein, we found that M2‐EVs could induce direct reprogramming of OCPs into M2-like macrophages to maintain balance. Materials and Methods: BMMs were cultured for 2 d in the presence of M-CSF and RANKL to differentiate into OCPs. RT-qPCR, WB and TRAP staining to detect OCPs differentiation preference after M2-EVs treatment. The transcriptomic analysis was conducted to determine the specific mechanisms. MitoSOX. In JC-1 staining and seahorse assay was also used to determine the mitochondrial indices. M2‐EVs were applied to ovariectomized (OVX) mice in vivo. Results: The histological data and molecular evaluation supported that M2-EVs decreased in the expression of genes typifying the OC lineage and increased expression of genes specific to M2 macrophages. The transcriptomic analysis was consistent with the results above and suggested that M2-EV treatment controls bone-related cells from a metabolic perspective. MitoSOX and JC-1 staining revealed mitochondria of OCPs with M2-EVs displayed higher membrane potential and lower MitoSOX levels. Seahorse assay showed a significant increase in mitochondrial OCR after M2-EVs treatment. MicroCT and the histological data showed that M2-EVs could alleviate osteoporosis. Conclusions: This study reports that M2‐EVs through improving OXPHOS, could induce reprogramming of OCPs into M2-like macrophages to maintain balance, which proposes a novel strategy that guides the transformation of bone-damaging cells into bone-repairing cells to alleviate osteoporosis via EVs.